Implementasi Pembelajaran Inkuiri Terbimbing Berbasis Information Technologi (IT) Untuk Meningkatkan Kreativitas Dan Hasil Belajar Siswa - Indra Hernawan; Sulistyono Sulistyono; Mulyati Sarifin (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2018)
This study aimed to obtain comparative increase in the creativity of the students who get a guided inquiry learning with students getting conventional learning. The method used is a quasi experiment conducted on students in one elementary school in Indramayu, West Java province with a number of 32 students. The research data was collected through a written test (posttest), observation, and questionnaire responses of teachers and students on the use of virtual simulation media in guided inquiry learning. Learning model inquiry guided to a class experiment, which lasted for three meetings, and begins with the initial tests and ends with a final test showed that there were differences in the ability of the creativity of students in both classes with a mean final test students' creativity 83.64 for an experimental class and the average class before 53.54 , Conclusions drawn based on the results of data processing and analysis using statistical Mc Nemar: 6.604, to the achievement of creative abilities of students obtained results that increase the ability of creativity of students in the experimental class with previous classes differ significantly. So that the application of guided inquiry learning model with the approach of inquiry on the subject of breathing in humans can be further increased kankarakter creativity and student learning outcomes compared with conventional learning. Most of the students are motivated to take an active role in the learning process, and wants Application of IT-based guided inquiry models that could be applied to other biological materials. Thus the adoption of the model IT-based guided inquiry can effectively enhance the creativity and student learning outcomes and provide a positive stimulus for students to learn biology Keywords : Based guided inquiry, Information Technologi (IT) This study aimed to obtain comparative increase in the creativity of the students who get a guided inquiry learning with students getting conventional learning. The method used is a quasi experiment conducted on students in one elementary school in Indramayu, West Java province with a number of 32 students. The research data was collected through a written test (posttest), observation, and questionnaire responses of teachers and students on the use of virtual simulation media in guided inquiry learning. Learning model inquiry guided to a class experiment, which lasted for three meetings, and begins with the initial tests and ends with a final test showed that there were differences in the ability of the creativity of students in both classes with a mean final test students' creativity 83.64 for an experimental class and the average class before 53.54 , Conclusions drawn based on the results of data processing and analysis using statistical Mc Nemar: 6.604, to the achievement of creative abilities of students obtained results that increase the ability of creativity of students in the experimental class with previous classes differ significantly. So that the application of guided inquiry learning model with the approach of inquiry on the subject of breathing in humans can be further increased kankarakter creativity and student learning outcomes compared with conventional learning. Most of the students are motivated to take an active role in the learning process, and wants Application of IT-based guided inquiry models that could be applied to other biological materials. Thus the adoption of the model IT-based guided inquiry can effectively enhance the creativity and student learning outcomes and provide a positive stimulus for students to learn biology.